The Extended Mobile Health Acceptance Model in Thailand: A Conceptual Framework - Paneepan Sombat; Wornchanok Chaiyasoonthorn; Singha Chaveesuk (My University, 2019)
Information technology has revolutionized people's lifestyle.People have the liberty of using the smart technology for reapings its benefits especially related to health care.The government of Thailand wants to optimize its benefit with the adoption of this technological advancement in the field of health care service in line with Thailand industry 4.0 policy and digital economy.Mobile health is one of the steps in this direction.However, less people in Thailand have performed on using mHealth services and limited research has been found under the acceptance of using mHealth technology.This study will help establish links to the general public and their accessibility and the ways to increase the usage rate.The mHealth acceptance framework is developed by integrating the Unified Theory of Acceptance and Use of Technology combined with self-efficacy, technology anxiety, and personal innovativeness in information technology.The contribution of this study is to build a proposed model for the mHealth acceptance and its use in Thailand.
Keywords: Conceptual model; Technology Acceptance Model; Health, Technology, Consumer Behavior